Advantages and disadvantages of container transportation system in maritime transportation - Ramadan Al-Jazairi, Prof. Dr. Hisham; Abdul Hussein Rmeish , Assist. Prof. Dr.Saddam (Basra studies journal, 2023)
The Advantages And Obstacles concerning The Maritime Transportation By containers System. This modest study does not cover all the Problems concerning this subject. But it draw the attention of the others to Present deep Studies in this Subject In Iraq the maritime transportation is underdeveloped and the use of containers in maritime transportation facing man's Problems e.g. the place of Containers Shipping, the unloaded Spaces inside the container Reshipping the containers‹ handling the Containers. Storage them On the other side there are many advantages Concerning the maritime transportation by containers system. Therefor we divided this research into three Sections: First Section: Sheed Light on the meaning of Container uses in maritime transportation Second Section! Discusses the advantages and problems faces maritime contain pin transportation. Third Section The effect of this kind of transportation on the traditional bill of Leading and the responsibility of the maritime Capper. Conclusion! Demonstrated the Research results and recommendations